2009
DOI: 10.1016/j.geb.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Group incentive compatibility for matching with contracts

Abstract: Hatfield and Milgrom (2005) present a unified model of matching with contracts, which includes the standard two-sided matching and some package auction models as special cases. They show that the doctor-optimal stable mechanism is strategy-proof for doctors if hospitals' preferences satisfy substitutes and the law of aggregate demand. We show that the doctor-optimal stable mechanism is group strategy-proof for doctors under these same conditions. That is, no group of doctors can make each of its members strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 23 publications
4
51
0
Order By: Relevance
“…Hatfield and Milgrom (2005) then extended this result to matching problems (with contracts) for which college preferences are substitutable and satisfy the law of aggregate demand. For the same setting, Hatfield and Kojima (2009) showed that these assumptions actually guarantee group strategyproofness.…”
Section: The College Proposing Deferred Acceptance Algorithmmentioning
confidence: 97%
“…Hatfield and Milgrom (2005) then extended this result to matching problems (with contracts) for which college preferences are substitutable and satisfy the law of aggregate demand. For the same setting, Hatfield and Kojima (2009) showed that these assumptions actually guarantee group strategyproofness.…”
Section: The College Proposing Deferred Acceptance Algorithmmentioning
confidence: 97%
“…Our setup can be trivially embedded in the many-to-one matching model with contracts of Hatfield and Kojima (2009), so the conclusion follows.…”
Section: Proof Of Theoremmentioning
confidence: 70%
“…24 School segregation can be purely racial or, as in Echenique, Fryer and Kaufman (2006), school segregation is measured according to the spectral segregation index of Echenique and Fryer (2006) which uses the intensity of social interactions among the members of a group (see also Cutler and Glaeser (1997)). 25 One benefit of hard bounds is that, it is straightforward to check whether they are implemented or not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations